Congenital and neonatal lupus erythematosus: two case reports Lúpus eritematoso congênito e neonatal: relato de dois casos - Marcos Noronha Frey; Ana Elisa Empinotti Ioppi; Gabriela Czarnobay Garbin; Roque Domingos Furian; Ana Elisa Kiszewski Bau (Sociedade Brasileira de Dermatologia, 2012)
Neonatal lupus erythematosus is an autoimmune disease produced by the passage of maternal antinuclear antibodies and extractable nuclear antigen antibodies through the placenta. At the moment of the diagnosis, the mothers are asymptomatic in 40 to 60% of cases. The most common manifestations are cutaneous lesions and congenital heart block. The cutaneous findings are variable and usually begin within the first weeks or months of life. Congenital lupus erythematosus is a congenital variant of neonatal lupus erythematosus. We present one case of congenital lupus erythematosus and one case of neonatal lupus erythematous, showing the variability of this disease. Lúpus eritematoso neonatal é uma doença auto-imune produzida pela passagem de anticorpos maternos antinucleares e anticorpos contra antígenos extraíveis nucleares através da placenta. No momento do diagnóstico, as mães são assintomáticas em 40 a 60% dos casos. As manifestações mais comuns são lesões cutâneas e bloqueio cardíaco congênito. Os achados cutâneos são variáveis e geralmente começam nas primeiras semanas ou meses de vida. Lúpus eritematoso congênito é uma variante do lúpus eritematoso neonatal. Apresentaremos um caso de lúpus eritematoso congênito e um caso de lúpus eritematoso neonatal, mostrando a variabilidade da doença.